2021
DOI: 10.3390/medicina57121323
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO Blood Type with Bleeding Severity in Patients with Acute Gastroesophageal Variceal Bleeding

Abstract: Background and Objectives: ABO blood types have been implicated as potential risk factors for various hemorrhagic diseases. No study has investigated the association between gastroesophageal variceal bleeding and ABO blood types. We aimed to evaluate the impact of ABO blood types on mortality and bleeding risk in acute gastroesophageal variceal bleeding. Materials and Methods: This is a retrospective observational study. Patients presenting with acute gastroesophageal varices bleeding diagnosed by endoscopy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Van Gieson's and Picro Sirius red staining were used for the assessment of collagen. The sections stained in Picro Sirius red were further observed under interference and polarized light that improves the visualization and assessment of collagen fibers using a Biolar microscope (BIOLAR, Warsaw, Poland) [30,31,49]. The density of connective tissue fibers appearing in Van Gieson's and Picro Sirius red staining was graded semiquantitatively from 0 to 4, where: 0-loose, 1-minimally dense, 2moderately dense, 3-markedly dense, and 4-very dense.…”
Section: Histopathological and Histochemical Investigation Of Anorect...mentioning
confidence: 99%
See 2 more Smart Citations
“…Van Gieson's and Picro Sirius red staining were used for the assessment of collagen. The sections stained in Picro Sirius red were further observed under interference and polarized light that improves the visualization and assessment of collagen fibers using a Biolar microscope (BIOLAR, Warsaw, Poland) [30,31,49]. The density of connective tissue fibers appearing in Van Gieson's and Picro Sirius red staining was graded semiquantitatively from 0 to 4, where: 0-loose, 1-minimally dense, 2moderately dense, 3-markedly dense, and 4-very dense.…”
Section: Histopathological and Histochemical Investigation Of Anorect...mentioning
confidence: 99%
“…Pathophysiological studies highlight increased abdominal pressure as a significant factor [2,11,25,26], along with hyperperfusion, neovascularization [7,27], overexpression of inflammatory mediators [21], and dysbiosis [28]. Histopathological changes include the deterioration of anchoring connective tissue with reduced collagen content and altered collagen ratios [24,[29][30][31]. All these factors collectively weaken the perivascular connective tissue and lead to the dilation of blood vessels, resulting in the formation of hemorrhoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is known that platelet function is more limited in patients with O blood group than in patients with other blood groups, which increases the potential for bleeding 10 . In the literature, studies have reported that patients with O blood group have more bleeding complications than those with other blood groups in various diseases such as variceal GI bleeding, postpartum hemorrhage, and severe traumatic bleeding [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Hematological abnormalities are also a matter of discussion in the daily clinical practice of emergency departments for both children [ 21 ] and adults with several comorbidities, such as liver diseases or portal hypertension [ 22 ].…”
mentioning
confidence: 99%